2002
DOI: 10.1046/j.1365-2826.2002.00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cAMP‐Response Element Binding Protein in Corticotropin‐Releasing Factor (CRF)‐Induced Down‐Regulation of CRF Receptor 1 Gene Expression in Rat Anterior Pituitary Cells

Abstract: Corticotropin-releasing factor (CRF) is a major secretagogue of adrenocorticotopic hormone from the anterior pituitary and a key activator of the hypothalamic-pituitary-adrenal axis. We previously reported that CRF down-regulates expression of the CRF type-1 receptor (CRF-R1) mRNA in cultured rat anterior pituitary cells. The present study was conducted to clarify the signal transduction systems involved in CRF-induced down-regulation of CRF-R1 gene expression in the anterior pituitary. Northern blot analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 42 publications
1
12
1
Order By: Relevance
“…During chronic opiate exposure, an increase in cellular adenosine 3′,5′-monophosphate (cAMP) activities is a celluar measure to counter the inhibition of cAMP by opiates [50]. Therefore, the downregulation of CRF-R1 mRNA expression during morphine withdrawal is also a postulated homeostatic adaptation to counteract the overactivation of cAMP [51]. In addition, we also showed here that mitragynine significantly lowered the mRNA levels of both CRF-R1 and CRF-R2 in morphine-withdrawn fish, a trend that correlates with the attenuation of both anxiety behavior and whole cortisol production.…”
Section: Discussionmentioning
confidence: 99%
“…During chronic opiate exposure, an increase in cellular adenosine 3′,5′-monophosphate (cAMP) activities is a celluar measure to counter the inhibition of cAMP by opiates [50]. Therefore, the downregulation of CRF-R1 mRNA expression during morphine withdrawal is also a postulated homeostatic adaptation to counteract the overactivation of cAMP [51]. In addition, we also showed here that mitragynine significantly lowered the mRNA levels of both CRF-R1 and CRF-R2 in morphine-withdrawn fish, a trend that correlates with the attenuation of both anxiety behavior and whole cortisol production.…”
Section: Discussionmentioning
confidence: 99%
“…The CRF R1 is coupled to the stimulatory G protein Gα s and can thus activate PKA and subsequently CREB (Kasagi et al , 2002). We found that treatment with a CRF R1 antagonist before stress exposure blocked the ability of FS to lead to increased levels of pCREB within a discrete set of brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, CRF receptor type 1 (CRF R1 ) mediates neuroendocrine and behavioral responses to stress as well as to drugs of abuse. The activation of CRF R1 stimulates the G protein G αs , leading to the activation of Protein Kinase A, and the transcription factor CREB (Kasagi, et al , 2002; Mcevoy, et al , 2002). As chronic stress has been shown to increase pCREB expression (Kwon, et al , 2006), examining the role of CRF R1 activation in the ability of FS to induce phosphorylation of CREB could help delineate the signaling pathways underlying stress-induced augmentation of cocaine reward.…”
Section: Introductionmentioning
confidence: 99%
“…The perisynaptic and subsynaptic distributions of CRFr labeling at excitatory synapses suggests that the activation of the CRF receptors affects excitatory postsynaptic currents. This modulation may reflect, in part, the activation of cAMP response element-binding protein (CREB; Kasagi et al, 2002). In other limbic brain regions, CREB is actively involved in the regulation of the expression of AMPA GluR1 subunits that are essential for AMPA receptor-mediated glutamatergic transmission (Olson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%